The Impact of Mental Health Campaigns on Self-Identification with Mental Illness, Perceived Control over Problems, and Perceived Need for Professional Treatment - Svitak, Katelyn (My University, 2025)
It has been speculated that increased mental health awareness, with a focus on mental wellbeing, is inadvertently contributing to the reported rise in mental health problems through the overinterpretation of minor distress as symptoms of mental illness. This study aimed at testing this hypothesis by examining the impact of a common mental health disorder (anxiety) campaign and a more severe disorder (schizophrenia) campaign on self-identification with mental illness. Additionally, this study examined the impact of self-identifying with mental illness on perceived control over problems and perceived need for professional treatment. As hypothesized, individuals exposed to the anxiety campaign reported higher self-identification with mental illness than individuals exposed to the schizophrenia campaign. Additionally, higher self-identification with mental illness was associated with lower perceived control over problems and higher perceived need for professional treatment. These findings increase current understanding on the impact of mental health campaigns and implications of self-identifying with mental illness.